Evidence Levels for Neuroradiology Articles: Low Agreement Among Raters - Ramalho, J (2015)
BACKGROUND AND PURPOSE: Because evidence-based articles are difficult to recognize among the large volume of publications available, some journals have adopted evidence-based medicine criteria to classify their articles. Our purpose was to determine whether an evidence-based medicine classification used by a subspecialty-imaging journal allowed consistent categorization of levels of evidence among different raters. MATERIALS AND METHODS: One hundred consecutive articles in the American Journal of Neuroradiology were classified as to their level of evidence by the 2 original manuscript reviewers, and their interobserver agreement was calculated. After publication, abstracts and titles were reprinted and independently ranked by 3 different radiologists at 2 different time points. Interobserver and intraobserver agreement was calculated for these radiologists. RESULTS: The interobserver agreement between the original manuscript reviewers was -0.2283 (standard error = 0.0000; 95% CI, -0.2283 to -0.2283); among the 3 postpublication reviewers for the first evaluation, it was 0.1899 (standard error = 0.0383; 95% CI, 0.1149-0.2649); and for the second evaluation, performed 3 months later, it was 0.1145 (standard error = 0.0350; 95% CI, 0.0460-0.1831). The intraobserver agreement was 0.2344 (standard error = 0.0660; 95% CI, 0.1050-0.3639), 0.3826 (standard error = 0.0738; 95% CI, 0.2379-0.5272), and 0.6611 (standard error = 0.0656; 95% CI, 0.5325-0.7898) for the 3 postpublication evaluators, respectively. These results show no-to-fair interreviewer agreement and a tendency to slight intrareviewer agreement. CONCLUSIONS: Inconsistent use of evidence-based criteria by different raters limits their utility when attempting to classify neuroradiology-related articles.